From Labral Tears to Bone Loss: Imaging the Spectrum of Shoulder Instability - Serfaty, Aline; Cantarelli Rodrigues, Tatiane; Afonso, P. Diana (Seminars in Musculoskeletal Radiology, 2025)
Glenohumeral instability results from disruptions in dynamic and static stabilizers of the glenohumeral joint, leading to dislocation, subluxation, or chronic apprehension. Although anterior glenohumeral instability is the most common form, posterior instability represents a distinct and often underrecognized condition with unique biomechanical and clinical characteristics. Imaging plays a critical role in evaluating shoulder instability, guiding diagnosis, and informing treatment decisions. Radiographs, computed tomography, and magnetic resonance imaging help assess structural abnormalities, such as labral tears, capsuloligamentous injuries, and osseous defects. Advanced imaging techniques, such as three-dimensional computed tomography and zero echo time magnetic resonance imaging, offer improved assessment of bone loss; magnetic resonance arthrography enhances the detection of soft tissue pathology. This article offers a comprehensive review of the imaging spectrum of glenohumeral instability, covering labral pathology, capsuloligamentous injuries, and bone loss. It highlights the critical role of precise imaging assessment in guiding optimal management strategies for both anterior and posterior instability patterns.
Keywords: glenohumeral instability; labral tears; Hill-Sachs lesion; Bankart lesion; glenoid track